Article RETRACTED due to malpractice The Effect of Dribbling Training Methods, Speed, and Leg Length on Players Dribbling Skills at the UPG 1945 NTT Futsal Club: A SEM-PLS Analysis - Dixon E.M. Taek Bete; Mugiyo Hartono; Hadi; Heny Setyawati; Ricko Irawan; Ridwan Sinurat (Retos, 2026)
Research Method, A quantitative approach using partial least squares structural equation modeling (SEM-PLS) is employed to analyze the influence of dribbling and speed drills on the dribbling skills of players on the UPG 1945 NTT futsal team. The research results, show that the “Dribbling Drills” variable does not have a significant effect on players’ dribbling ability, with a path coefficient of -0.057, a t-statistic of 0.247, and a p-value of 0.805. In contrast, the variable “Speed Drills” has a positive and significant influence on dribbling ability, with a path coefficient of 0.378, a t-statistic of 2.433, and a p-value of 0.015. The R-squared value of 0.130 indicates that both variables together explain only 13% of the players’ dribbling ability. Research analysis, This demonstrates that speed drills contribute most significantly to improving dribbling ability, as they help increase players’ acceleration, motor coordination, and agility while carrying the ball. Research conclusion, This demonstrates that speed drills are the factor that most influences the improvement of futsal players’ dribbling skills; therefore, they should form the core of the UPG 1945 NTT futsal team’s training program.